Photocatalytic Activity Enhancement of Titanium Dioxide Nanoparticles Degradation of Pollutants in Wastewater - A. Barakat, Mohamed; Kumar, Rajeev; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this brief, a comprehensive review of the UV/visible-TiO2 photocatalytic oxidation process is presented with an insight into the mechanisms involved, the role of titanium dioxide as a catalyst, irradiation sources, types of reactors, and a comparison between various modes of TiO2 application. An overview of the development and enhancement of the activity of TiO2 nanoparticles in photocatalysis is presented. The topics covered include a detailed look at the unique properties of the TiO2 nanoparticles and their relationship to photocatalytic properties. The utilization of the TiO2 nanoparticles as photocatalysts, in the non-doped and doped forms is also reviewed. Finally, the use of modified TiO2 nanoparticles has made a significant contribution in providing definitive mechanistic information regarding the visible light photocatalytic processes.
Introduction -- Fundamentals and mechanism of TiO2 photocatalysis -- Photocatalysis enhancement routes.-ApplicationsWastewater treatment -- Visible light photocatalysis -- Conclusions.
Keywords: Chemistry, Technical; Water; Hydrology; Nanotechnology; Environmental chemistry; Industrial Chemistry; Water; Nanotechnology; Environmental Chemistry